Zinc (organic and inorganic) modulates the expression of catalase and glutathione peroxidase genes related to the antioxidant system of Apis mellifera forager bees - Moreira, Iloran do Rosario Correa [UNESP]; Kadri, Samir Moura [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (Alma Mater Studiorum, Univ Bologna, 2024)
In Apis mellifera the activity performed by individual worker bees as brood nutrition, defence and foraging, is regulated by physiological age or colony needs, a phenomenon referred to as polyethism. Bees forage long distances in search of resources for colony maintenance, which increases their metabolism levels due to the expenditure of energy during the activity. After two weeks offoraging activities, proteins affected by oxidative stress accumulate in the brain, and cognitive capacity declines. Although bee diet is focused on high energy and protein foods, other nutrients, such as vitamins and minerals, are essential for colony development. Zinc (Zn) is a vital structural and functional component of organisms. Oxidative stress can occur under Zn deficiency, and Zn supplementation can help prevent oxidative stress-induced damage in different cells and tissues. Therefore, the aims of the present study were to verify if Zn supplementation (inorganic and organic forms) can modulate the antioxidant system of forager bees. This was assessed by analysing catalase (CAT) and glutathione peroxidase (GPX) gene expression. Following organic Zn supplementation, increased expression of GPX was observed, with significant difference from those in the control and inorganic Zn treatments. Conversely, there was an increase in CAT expression under inorganic Zn supplementation, with a significant difference from those in the control and organic Zn treatments. Zn, regardless of the source, did not have harmful effects on the colonies and could modulate the expression of antioxidant system genes
Keywords: gene expression; longevity; mineral; nutrition